Гелиэя – выборный суд в Афинах VI–V вв. до н. э. - Semenov I. V. (Winter school marathon, 2017)
This article presents the author's view on one of the most important stages in the development of the state and the right - the electoral court in Athens VI-V century BC: its essence and meaning.
Keywords: Древняя Греция; Ancient Greece; Гелиэя; выборный суд; Афины; Geliee; electoral court; Athens